The Alien City chronotope within the scope of Toni Morrison’s Jazz - Chernetsova, Ekaterina; Maslova, Elizaveta (Penerbit Universiti Kebangsaan Malaysia, 2019)
The research observes the representation of the alien city chronotope in Jazz (1992) by a contemporary American writer Toni Morrison. The narration of the novel occurs in Harlem (New York) in the 1920-s, however, because most characters’ identities originate in the mid-19th-century American South, time and space frames extend. Focusing on the city space in the novel Jazz we regard the city as a social and cultural phenomenon of America, an independent live character that enters into a dialogue with the novel’s protagonists and, at the same time, contributes to their alienation within its frames. Harlem of 1920s functions not only as sociohistorical background but also as a unique narrator that relates the urban experience of African- Americans. We deduce that the chronotope exhibited in the novel in question combines several places and embodies narration about protagonists’ roots, their original habitat and a new conflicting environment that both attracts and repels them. The intrinsic ties of time and space in the literary work discussed in the article are presented on the level of the city, which represents alien and fragmentized reality. Thus we are convinced that the alien city chronotope in the novel is shaped by the opposition of ethnic and cultural identities of characters within their changing world. The characters’ illusions and aspirations are guided by the dubious and forceful voice of the city and none of the protagonists is able to escape the traumatic labyrinth of time and space tracing their memory.